The integrity of air pollution data measurements and their legal implications, a case study in Qatar on air pollution of the French company plume labs - Kattan, Imad AbdelKarim; Iftaihat, Yassir Al; El Farag, Mohamed Salem Abou (Edelweiss Applied Science and Technology, 2024)
Countries today face immense environmental challenges, with the safety and sustainability of the environment at the forefront of their priorities. Nations, such as Qatar, are committed to addressing air pollution, a significant environmental hazard. To ensure the accuracy of air pollution data, Qatar relies on robust environmental measurement standards, with government institutions playing a crucial role in monitoring and reporting this data. However, the emergence of private companies like Plume Labs, which provide air pollution data for various countries, has raised significant concerns about data accuracy and credibility. These concerns can adversely affect the reputation of nations and impede investment. Notably, Plume Labs has openly stated that it does not guarantee the accuracy of its data, which poses risks to national sovereignty and the integrity of pollution data. Furthermore, there is a lack of clarity regarding the legal recourse available to countries or entities affected by potentially inaccurate data from companies like Plume Labs. Therefore, it is essential to establish a legal framework to regulate the provision of air pollution data by private companies. This framework should include evaluating the accuracy and reliability of data provided by companies such as Plume Labs and determining their legal liability for disseminating inaccurate air pollution information.